KEWAJIBAN PELAKU USAHA KOLAM RENANG DALAM PEMENUHAN STANDAR BAKU MUTU KESEHATAN AIR TERHADAP KOSNUMEN (Solusi, 2023)
The obligation of business actors to meet swimming pool health quality standards is to fulfill consumer rights. Fulfillment of water health is aimed at preventing the occurrence of actors that result in the use of water that is not in accordance with quality standards. This study uses empirical normative methods, namely starting from positive legal provisions that apply to concrete events in society. The results of this study can be concluded that in fulfilling swimming pool health requirements business actors must carry out standard operating procedures carried out in accordance with applicable regulations covering physical, biological, chemical parameters. In carrying out activities, swimming pool business actors have forms of supervision, one of which is implementing quality standards for swimming pool water. And realizing the rights of consumers as users of swimming pool services in fulfilling the service quality requirements for swimming pool water health.